Phase Transition and Superconductivity Enhancement in Se‐Substituted MoTe2 Thin Films. Issue 48 (9th October 2019) - Li, Peiling; Cui, Jian; Zhou, Jiadong; Guo, Dong; Zhao, Zhenzheng; Yi, Jian; Fan, Jie; Ji, Zhongqing; Jing, Xiunian; Qu, Fanming; Yang, Changli; Lu, Li; et al.
Abstract: Consecutively tailoring few‐layer transition metal dichalcogenides MX2 from 2 H to T d phase may realize the long‐sought topological superconductivity in a single material system by incorporating superconductivity and the quantum spin Hall effect together. Here, this study demonstrates that a consecutive structural phase transition from T d to 1 T ′ to 2 H polytype can be realized by increasing the Se concentration in Se‐substituted MoTe2 thin films. More importantly, the Se‐substitution is found to dramatically enhance the superconductivity of the MoTe2 thin film, which is interpreted as the introduction of two‐band superconductivity. The chemical‐constituent‐induced phase transition offers a new strategy to study the s +− superconductivity and the possible topological superconductivity, as well as to develop phase‐sensitive devices based on MX2 materials. Abstract : Consecutively tailoring few‐layer transition metal dichalcogenides from the 2H to Td phase may realize the long‐sought topological superconductivity by incorporating the quantum spin Hall effect and superconductivity. This study demonstrates that the transitions from Td to 1T' to 2H phase can be realized in Se‐substituted MoTe2 thin films. More importantly, the observed superconductivity enhancement can be interpreted as two‐band superconductivity.